1991
DOI: 10.1002/jnr.490300402
|View full text |Cite
|
Sign up to set email alerts
|

A subpopulation of bone marrow‐derived macrophage‐like cells shares a unique ion channel pattern with microglia

Abstract: Rat microglia share a number of antigenic, functional, and morphological similarities with macrophages from other tissues, but are characterized by a distinctly different pattern of ion channels in the cellular membrane (Kettenmann et al., J Neurosci Res 26:278-287, 1990). Macrophages typically express outward and inward K+ currents. In contrast, microglia lack outward currents and only show inwardly rectifying K+ currents, regardless of the isolation or cultivation method employed for microglia. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…High extracellular potassium levels, as found in ischemic tissue, potentiate glutamate release from microglia that are particularly sensitive to changes in potassium levels because of their lack of a substantial potassium outward current. 26 A recent study has suggested that microglia are capable of contributing to the development of the ischemic infarct at time points similar to those in the present study. 27 However, the conclusion was based on the expression of interleukin-1␤ and Bax in microglia within the zone of injury rather than from the results of an intervention strategy.…”
Section: Marks Et Al Microglial Response To Cerebral Ischemia In Shrssupporting
confidence: 85%
“…High extracellular potassium levels, as found in ischemic tissue, potentiate glutamate release from microglia that are particularly sensitive to changes in potassium levels because of their lack of a substantial potassium outward current. 26 A recent study has suggested that microglia are capable of contributing to the development of the ischemic infarct at time points similar to those in the present study. 27 However, the conclusion was based on the expression of interleukin-1␤ and Bax in microglia within the zone of injury rather than from the results of an intervention strategy.…”
Section: Marks Et Al Microglial Response To Cerebral Ischemia In Shrssupporting
confidence: 85%
“…Following LPS stimulation, microglia are transformed into a reactive state that is characterized electrophysiologically by the expression of the K+ OR (Niirenberg et al, 1992), which is lacking in most nonstimulated microglia (Kettenmann et al, 1990;Banati et al, 1991). The presence of this K+ OR is a robust indicator of the functional state of the cell (Fischer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Giulian et al (1995) found that mononuclear phagocytes isolated from the brain of newborn rats gave rise to cells with particular morphological features which did not appear in cultured mononuclear phagocytes from non-nervous sources; these authors concluded that microglial precursors are a unique class of cell di erent from precursors of other types of mononuclear phagocytes. In this connection, it was found that a subpopulation of bone marrow-derived cells showed the same ion channel pattern as microglial cells, suggesting that the bone marrow contains precursors that are committed to produce microglia and that they are di erent from the precursors which produce macrophages for other body regions (Banati et al, 1991).…”
Section: Origin From Monocytes/macrophagesmentioning
confidence: 98%